7(y-6)+3y=10(y+1)

Simple and best practice solution for 7(y-6)+3y=10(y+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(y-6)+3y=10(y+1) equation:


Simplifying
7(y + -6) + 3y = 10(y + 1)

Reorder the terms:
7(-6 + y) + 3y = 10(y + 1)
(-6 * 7 + y * 7) + 3y = 10(y + 1)
(-42 + 7y) + 3y = 10(y + 1)

Combine like terms: 7y + 3y = 10y
-42 + 10y = 10(y + 1)

Reorder the terms:
-42 + 10y = 10(1 + y)
-42 + 10y = (1 * 10 + y * 10)
-42 + 10y = (10 + 10y)

Add '-10y' to each side of the equation.
-42 + 10y + -10y = 10 + 10y + -10y

Combine like terms: 10y + -10y = 0
-42 + 0 = 10 + 10y + -10y
-42 = 10 + 10y + -10y

Combine like terms: 10y + -10y = 0
-42 = 10 + 0
-42 = 10

Solving
-42 = 10

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 11+18=x+19 | | (2/9)g=8 | | 9(4x+1)=10(3x+2) | | 0.029x+2x=0.034x | | 2849=37(p+20) | | f(x)=2t-3whatisf(7) | | -3x+5=-2(3x+5) | | 15+(-5x)=15-5x | | 3y+4=-1y+-4 | | -7u+11=-9(u-1) | | 0.029+2x=0.034x | | 2x(2x-5)(5x+2)=0 | | 8(-9p+2)-7p= | | 814=-22a | | -2(x-7)=-4x+20 | | 5v-89=2v+34 | | 3n+35=7n+35 | | 9w-10=2(w+9) | | 5+x^2=65 | | -2x+5=20-x | | 3x(x+2)=3x^2+4x-3+2x | | -3(5y-2)-y=-2(y-2) | | 23=3u+8 | | 8x-3.4=3x-6.7 | | -8d-d+7d=72 | | (w-4/-9)(-2/-3) | | -5(y-3)=-15 | | -8u+2(u+5)=16 | | 2x+3-5=5x-3+3x | | 7-4x=5x | | 2y+3(y-2)=29 | | C=240+0.75Y |

Equations solver categories